Legal Protection for Student Interns from the Perspective of Law in Indonesia - Nadia Intan Ceria (Media Hukum Indonesia (MHI), 2026)
Internship programs are initiatives designed to enhance skills; however, their implementation often presents various challenges. The purpose of this study is to examine how Indonesian labor law protects students from a labor law perspective. The approach used is a normative legal analysis, focusing on statutory regulations, particularly â€œLaw No. 13 of 2003 on Manpowerâ€ and â€œMinister of Manpower Regulation No. 6 of 2020.â€ The data collected is secondary, sourced from literature reviews. The results of the study indicate that legal protection for interns includes provisions regarding rights and obligations, stipends, occupational safety and health, and social security; however, strengthened oversight and enforcement are necessary to ensure that these programs continue to function as effective training tools and do not evolve into the exploitation of interns.